GAMBARAN KEAKTIFAN BELAJAR TARUNA TEKNIKA PADA PERKULIAHAN MEKANIKA TERAPAN - Lusiani Lusiani; Andi Hendrawan; Gilang Meilanda Kurniawan (KOLONI, 2022)
Learning media is one of the things that triggers learning activities and allows the realization of good learning objectives, so the author is interested in providing an overview of the learning activities of technical cadets in applied mechanics lectures. The method in this study is a survey and literature review. The object of research is the cadets of the AMN Cilacap engineering study program. Learning outcomes in the psychomotor domain are obtained through the discussion method. The instrument used is using google classroom media. Observations were made according to the indicators of learning activity using video media. In general, the indicators of activity have been seen, but still not overall. This means that learning activity has not been maximized or it can be said that technical cadets are active in applied mechanics lectures.  Keywords: description, active learning, applied mechanics